2017
DOI: 10.1016/j.soilbio.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of drought tolerance traits for microbial decomposition in the DEMENT model

Abstract: The frequency and intensity of drought are expected to increase in the future, yet the consequences for soil microbial communities and functioning remain unclear. Processes such as decomposition could be maintained if microbial communities become more drought tolerant. However, increased drought tolerance might involve physiological costs with uncertain consequences for ecosystem processes. Here we used the trait-based model DEMENT to quantify the sensitivity of microbial traits, community dynamics, and litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…The observations of community shifts suggests environmental pressures that select for taxa that can survive the physiological stress imposed by drought [36][37][38][39] . The community shifts could also be ascribed to the indirect effect of drought-induced changes in plant litter chemistry acting as a selection pressure 7,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The observations of community shifts suggests environmental pressures that select for taxa that can survive the physiological stress imposed by drought [36][37][38][39] . The community shifts could also be ascribed to the indirect effect of drought-induced changes in plant litter chemistry acting as a selection pressure 7,21 .…”
Section: Discussionmentioning
confidence: 99%
“…A model-based analysis demonstrated that adaptive microbial responses to C limitation and water stress might emerge from microbial traits related to dormancy and production of extracellular polymeric substances (Brangarí et al, 2018). The importance of community-level regulation and microbial trait trade-offs was highlighted by trait-based modeling of litter decomposition (Kaiser et al, 2015;Allison and Goulden, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate that these approaches will improve our understanding of the physiological constraints facing microbes under anthropogenic influence. By linking population-level response traits to community Figure 3: Summary of the proposed trait-based framework incorporating microbial life history strategies into the DEMENT model to predict community response and its ecosystem consequences under environmental change (adapted from Allison and Goulden, 2017). and ecosystem processes, our life history theory can improve predictive understanding of soil C responses to future climatic change.…”
Section: Discussionmentioning
confidence: 99%
“…Yield in the model is a function of multiple factors, including substrate type and stoichiometry, enzyme production rates, uptake investment, and temperature. The most recent version of DEMENT also includes a simple representation of drought stress tolerance (Allison and Goulden, 2017). After incorporating trait tradeoffs derived from omics or other data sources for individual taxa, DEMENT projects community responses and carbon cycling consequences under simulated environmental conditions.…”
Section: Carbon Cycling Implications Of Tradeoffs In Y-a-s Traitsmentioning
confidence: 99%